Photoinduced electron transfer fluorimetric Hg(II) chemosensor based on a BODIPY armed with a tetrapod receptor - Culzoni, Maria Julia (2013)
From the great variety of BODIPY based-chemosensors able to determine Hg2+, only a small portion has been applied to its determination in environmental and/or biological samples. The lack of studies on the analytical performance of the latter sensors makes interesting the development of investigations oriented to their possible analytical applications. The synthesis of a BODIPY derivative armed with a tetrapod receptor is described. The procedure is based on a previous publication, and the modifications performed to improve the synthesis include alternative procedures with different objectives, as the consecution of a multigram synthesis, improving the low yields of some of the previously proposed procedure steps, simplifying the experimental steps, achieving the desired purity requirements for use with analytical purposes, and enriching the characterization of the implied structures. The characteristics of its selectivity towards Hg2+ have been investigated, and the OFF–ON fluorometric response, based on a photo-electron transfer (PET) mechanism, served as the base for the development of a method able to determine Hg2+ in environmental waters at ng mL−1 levels.